Zum Canettischen Literaturbegriff. Von der Topie zur Expressiven Kultur - Mausch, Krzysztof (Studia Germanica Posnaniensia, 2018)
The autbor reconstructs Canetti's conception of literature on the basis of his essays. This conception was developed in 1936. At its base there is a genetically anthropological conception. Canetti calls in question the immediate moral influence of literature, and what follows its specific role. In Canetti's conception of literature a desideratum is contained of a new vision of culture - expressive culture.